Analisis Manajemen Parking Stand Terhadap Keselamatan Pergerakan Pesawat Udara Di Bandara Udara Komodo Labuan Bajo - Amri Feisal Darjami; Annike Resty Putrie (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
Aviation safety, especially on the air side, is very important, so there is a need for supervision so that it can be maximized in maintaining the smooth running of activities on the apron, this has been regulated in Circular Letter Number 23 of 2011 concerning Improving Operational Safety at the Apron. One of the activities at Apron is the activity carried out by the Apron Movement Control Unit, namely determining the stand packing for the aircraft parking lot. Management Parking Stand which greatly determines safety in flight operations. Komodo Labuan Bajo Airport has 3 parking stands that are used for non-commercial planes such as private planes, private jets, however, all of these three parking stands cannot be used. from the parking stand because the wings between the two aircraft were too close or the sizes of the parking stands between A1, A2, and A3 were different sizes and the three parking stands are still actively used today. This study aims to determine parking stand management applied at Labuan Bajo Airport and parking stand management for the safety of aircraft movements at Komodo Labuan Bajo Airport.This study used a qualitative method with data collection methods in the form of observation, interviews, and documentation. Sources of data in this study were obtained from primary data and secondary data. This research was conducted from May to June 2023 at Labuan Bajo Airport.The results of this study Labuan Bajo Airport have 7 parking stands, of which 2 parking stands are used for garbarata, and 5 parking stands are used for remote and parking stands for charters where not many charter planes enter Labuan Bajo Airport and to maintain flight safety in determine the parking stand The AMC Unit is working according to the SOP that has been set. When there are planes that will be landing at the same time, the AMC Unit will ask the ATC for an estimate of the aircraft, then the AMC Unit will determine the parking stand based on the type of aircraft that will be landing, for parking stands 5 and 6 can be used for Boeing and Airbus aircraft, parking stand 3 is used for ATR type aircraft, and parking stands 6 and 7 can be used for Boeing or Airbus type aircraft.